Redesign of work facilities at the tofu pressing station with a participatory ergonomic approach - Erliana, Cut Ita; Sayuti, M.; Abdullah, Dahlan; Asral, Al; Siagian, Yusril Yahya (Edelweiss Applied Science and Technology, 2024)
Tahu Palda is a small and medium-sized micro business in the food industry that produces tofu. This factory has been producing tofu since 2005, located in North Aceh. The workers in this tofu usually five workers, with an average of 7 working hours per day. Based on the observations at several workstations, initial data indicate that the dominant work posture is standing, bending, and lifting heavy loads such as a 20 kg weight for pressing and lifting a mold holder with a 15 kg load. This is done continuously for 7 working hours each day. Based on the results of the distribution of the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), it was found that workers at the station experience complaints such as back pain, lower back pain, and upper arm pain due to the high frequency of lifting heavy loads. If this continues to be neglected, it can lead to work-related diseases such as musculoskeletal disorders. The assessment of workers’ posture using the Rapid Entire Body Assessment (REBA) method shows that the score obtained for the job of pouring soybean paste is 7, which means a moderate risk, the job of lifting the press weight is 5, which means a moderate risk, and the job of flipping molds has a score of 10, which falls into the high-risk category and needs improvement. Improvements were made using a participatory ergonomics approach, resulting in the decision to redesign the tofu press tool to fit the workers’ body anthropometry. The anthropometric calculations for the height range of the press support tool and cutting tool are 141.1 cm, the press support range is 68.78 cm, the width of the press tool is 49.4 cm, the height of the tray is 4.54 cm, and the height of the tray holder is 103.85 cm.